For whom the bell tolls? Methicillin-resistant Staphylococcus aureus infections in India - Mazhuvancherry Kesavan Unnikrishnan, Parambi Akhila Eldo, Stanly Elstin Anburaj, Prashant Chandra, Vilakkathala Rajesh, (Journal of Applied Pharmaceutical Science, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the common causes of infections in the contemporary era and a major contributor to hospital- and community-acquired infections. The repeated formation of epidemic strains is the main characteristic of epidemiology, despite its genetic diversity. The global and Indian prevalence varied from 13%–74% and 37%, respectively. Most clones independently acquire the staphylococcal cassette chromosome (SCCmec), which comprises genes encoding proteins that cause resistance to most β-lactam antibiotics. SCCmec types I, II, or III are found in most HA-MRSA strains, whereas SCCmec types IV or V are found in CA-MRSA. The major clone present in Indian hospitals is ST772-MRSA-V. These strains produce a vast array of virulence factors, including panton-valentine leucocidin toxins, and when paired with β-lactamase enzymes, most clones show high resistance to different antibiotic classes. Global mortality ranges between 15% and 60% and India witnessed less than 27% mortality. Treatment costs range from $3,220 to $9,388 globally, with an estimated $124 ($45–484) per patient cost in India. The evaluation of novel antibiotics and ancillary services (e.g., source control, and infectious disease consultation) is necessary for effective therapy, which is still difficult to achieve. This review summarizes the epidemiology, transmission, genetic diversity, surveillance, and management of MRSA from an Indian perspective.
Keywords: MRSA, prevalence, hospital-acquired MRSA, SCCmec types, PVL gene, mortality